The Effectiveness of a Psychoeducation Intervention Program for Enhancing Self-Esteem and Empathy : A Study of Emerging Adult College Student - Cathlin, Cintya Amelia; Salim, Rose Mini Agoes (Jurnal Paedagogy, 2024)
This research examines the effectiveness of psychoeducation intervention programs among emerging adult college students. We used the quantitative method with single-subject designs—Kirkpatrick evaluation model conducted by targeting two measurement levels: reaction and learning. Quantitative data analysis used the Rosenberg Self-Esteem Scale (RSES) and the Basic Empathy Scale (BES). Qualitative data were measured through baseline, treatment, and follow-up assessments. The findings of this research demonstrated that enhancing self-esteem and empathy through this program was effective. Significant changes in the subjects' knowledge and attitudes were observed after the intervention. This research suggests that emerging adult college students can gain a deeper understanding of their potential and experience a positive mind and emotional states through increased self-esteem and empathy.